Simulation and experimental study on the effect of iron on the structure and flow properties of coal ash slag. (5th June 2023) - Zhang, Linmin; Song, Xudong; Wei, Juntao; Yang, Jun; Lv, Peng; Su, Weiguang; Zhou, Ying; Yu, Guangsuo
Graphical abstract: Highlights: Effect of iron on slag fluidity was investigated using MD simulations and ring statistics. Effect of iron on slag viscosity was quantified by ring distribution. Existence of multi-membered rings led to poor fluidity of slag. Introduction of iron led to the transformation of multi-membered ring to low-membered ring. Relationship between viscosity and ring distribution was established. Abstract: Slag fluidity is an important parameter affecting the stable operation of the gasifier. Above liquid temperature, slag fluidity is closely related to its structure. In the present study, the effect of iron on the three-dimensional connection state between [SiO4 ] 4- and [AlO4 ] 5- tetrahedrons in the SiO2 -Al2 O3 -FeO-CaO slag system at 1773 K was deeply discussed by applying molecular dynamics (MD) simulation and ring statistics methods, and the slag network structure was divided into three rings with different functions according to the three-dimensional connection state. It was found that Fe 2+ operated as a network modifier ion and substituted Si 4+ and Al 3+ in the slag and combined with O 2–, thereby continuously depolymerizing higher-order rings into lower-order rings. This phenomenon simplified slag structure, reduced internal friction force, and improved fluidity. Finally, the ring distribution coefficient (Rdc ) was defined and it was found that there was a linear relationship between Rdc and viscosity.